PERENCANAAN PENJADWALAN PRODUKSI UNTUK MEMINIMALISIR KETERLAMBATAN PEMESANAN PADA PT XYZ - Pitaloka, Dia Ardiana; Widiasih, Wiwin (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
PT XYZ is a company operating in the furniture sector which produces tables, chairs and cupboards. This company's ordering system is make to order, both export and local. The production process at this company consists of 7 production process flows including the CPP process, wood process, assembly, sanding, painting, checking, packing. The production process takes place using 20 different types of machines. The problem faced by the company is delays in fulfilling orders that do not comply with the deadline provisions. This problem is caused by inefficient production scheduling, therefore researchers analyze production scheduling using the Campbell Dudeck Smith, Palmer and Dannenbring methods and analyze the costs. However, before scheduling machines, it is necessary to test data uniformity, adequacy, normal time and standard time. The aim of these three methods is to find the minimum makespan value. From the results of these calculations, the minimum Makespan value obtained from the CDS and Dannenbring methods is 813.33 hours in the order GFABCED, GFACBED, GFACEBD, GFBCAED, GFCABED, GFCBAED. If you use the company's calculation method, the makespan value is 1026 hours with details of 840 working hours and 186 overtime hours. The CDS and Dannenbring methods in the order GFABCED, GFACBED, GFACEBD, GFBCAED, GFCABED, GFCBAED require labor costs of Rp. 141,520,058, whereas if you use the company method the labor costs are Rp. 150,253,734 required. If compared, the savings cost is IDR 8,733,676 per worker.